eHealth in geriatric rehabilitation: an international survey of the experiences and needs of healthcare professionals - Kraaijkamp, Jules; Persoon, Anke; Aurelian, Sorina; Bachmann, Stefan; Cameron, Ian D.; Choukou, Mohamed-Amine; Dockery, Frances; Eruslanova, Kseniia; Gordon, Adam L.; Grund, Stefan; Kim, Hyub; Maier, Andrea B.; et al. (Journal of Clinical Medicine, 2023)
While eHealth can help improve outcomes for older patients receiving geriatric rehabilitation, the implementation and integration of eHealth is often complex and time-consuming. To use eHealth effectively in geriatric rehabilitation, it is essential to understand the experiences and needs of healthcare professionals. In this international multicentre cross-sectional study, we used a web-based survey to explore the use, benefits, feasibility and usability of eHealth in geriatric rehabilitation settings, together with the needs of working healthcare professionals. Descriptive statistics were used to summarize quantitative findings. The survey was completed by 513 healthcare professionals from 16 countries. Over half had experience with eHealth, although very few (52 of 263 = 20%) integrated eHealth into daily practice. Important barriers to the use or implementation of eHealth included insufficient resources, lack of an organization-wide implementation strategy and lack of knowledge. Professionals felt that eHealth is more complex for patients than for themselves, and also expressed a need for reliable information concerning available eHealth interventions and their applications. While eHealth has clear benefits, important barriers hinder successful implementation and integration into healthcare. Tailored implementation strategies and reliable information on effective eHealth applications are needed to overcome these barriers.